PENGARUH PENERAPAN ACTIVE, JOYFUL, AND EFFECTIVE LEARNING (AJEL) PADA MATERI PERUBAHAN LINGKUNGAN TERHADAP SIKAP PEDULI LINGKUNGAN SISWA - Supriyatin, S; Nurnawati, N; Heryanti, Erna (Universitas Negeri Jakarta, 2016)
The aim of the research was to analyze the effect of the application of Active, Joyful and Effective Learning (AJEL) to environmentally care attitude of students in X grade of 33 Senior High School of Jakarta. Sample was collected by a cluster random sampling technique with one experimental class, namely class X-Science 1, whereas X-Science 3 as control class with a total sample of 62. This study was a Quasi Experimental Method with Non-Randomized Control Group Pretest-Posttest Design. Components of learning model that reflects the Active, Joyful and Effective Learning (AJEL) that used in this research was time token, gallery walk, and outdoor learning. After doing normality test (Kolmogorov Smirnov Test) and homogeneous test (Fisher Test), known that data had normal distribution and homogeneous. Increase in environmentally care attitude measured use N-Gain test. Result of the test are, in experimental class, N-Gain score is 52,8 which includes into middle increased categories. In control class, N-Gain score is 24,8 which includes into low increased categories. Result of calculation hypothesis test (t-test) indicated there was an effect of the application of Active, Joyful and Effective Learning (AJEL) to environmentally care attitude of students.